Awareness on Constitutional Rights of Citizens and Form of Protection of Constitutional Rights of Citizens in Indonesia - Tafta Aji Prihandono; Sri Kusriyah Kusriyah; Widayati Widayati (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
In the Constitution of the Republic of Indonesia of 1945 Article 1 (3) explicitly states that Indonesia is a State of Law. One element that is owned by the state law is the fulfillment of basic human rights as expressed by Friedrich Julius Stahl. Efforts to achieve a constitution that can follow the progress and will meet the basic human rights, the constitution must have a dynamic aspect and were able to capture the phenomenon of historical change, so as to make it as a constitution that is always alive. Only problem is the performance of the Government as the executor of the constitution (executive, legislative and judicial) still do not provide justice and satisfaction for those seeking justice, therefore the necessary awareness of constitutional rights of citizens in Indonesia. Efforts to protect the constitutional rights of Indonesian citizens can be done through the court and non-court lines, and can also via maximize the role of the Constitutional Court to extend its authority. The expansion of the authority of the Constitutional Court may be to accommodate Constitutional Complaint and Constitutional Question.Keywords: Awareness; Constitutional Rights; Form of Protection.